Unødig lang sagsbehandlingstid i danske straffesager: - Kasper Jørgensen; Annette Olesen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract For many years the Danish criminal justice system has been criticized for its drawn out handling of criminal cases – which is not only problematic for the victim’s sense of justice, but is also a violation of the defendant’s civil rights. It is nevertheless surprising how little we know about the  implications for those who are forced to wait an unreasonably long time for trial, especially for those who are not remanded into custody. This article uses a socio-legal perspective to explore the time before conviction for defendants who must continue to live their everyday lives while awaiting decisions. Based on interviews (n=45) and judicial decisions we show that the interviewees awaiting their trial are trapped in a powerless position and are unable to take positive steps forward in their lives. Furthermore, the article shows that experiencing a drawn-out trial date has a negative influence on these citizens’ attachment to society even before their conviction by exposing them to social barriers similar to those faced by ex-convicts who have already served their time.